2021
DOI: 10.1038/s41598-021-01030-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct association between rainfall and non-typhoidal Salmonella bloodstream infections in hospital-admitted children in the Democratic Republic of Congo

Abstract: Non-typhoidal Salmonella (NTS) ranks first among causes of bloodstream infection in children under five years old in the Democratic Republic of Congo and has a case fatality rate of 15%. Main host-associated risk factors are Plasmodium falciparum malaria, anemia and malnutrition. NTS transmission in sub-Saharan Africa is poorly understood. NTS bloodstream infections mostly occur during the rainy season, which may reflect seasonal variation in either environmental transmission or host susceptibility. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Other non-typhoidal Salmonella serotypes were observed in the meat pathway too, but not ST313 [23]. Furthermore, a study in DR Congo showed a direct association of rainfall with iNTS, pointing to a possible waterborne environmental reservoir [69].…”
Section: The Present Findings Point To the Evidence Of An Animal Rese...mentioning
confidence: 91%
See 1 more Smart Citation
“…Other non-typhoidal Salmonella serotypes were observed in the meat pathway too, but not ST313 [23]. Furthermore, a study in DR Congo showed a direct association of rainfall with iNTS, pointing to a possible waterborne environmental reservoir [69].…”
Section: The Present Findings Point To the Evidence Of An Animal Rese...mentioning
confidence: 91%
“…Apart from rats, small rodents such as mice should be assessed, as well as lizards and geckos which are notable carriers of Salmonella too [77]. Food and water should be further assessed as a vehicle for transmission, including fork-to-farm studies along the meat pathway [23,78], crops and green leaves [13,69]. Source attribution studies such as case-control and outbreak investigation studies should complement the picture of iNTS transmission [13,78].…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…The reservoirs and transmission route of the pathogens responsible for iNTS in SSA remains unknown. Seasonal patterns of iNTS, and the close domestic association of humans and animals in parts of SSA might suggest that environmental factors could play a role [ 34 , 35 ]. However, numerous studies have failed to establish any convincing link between strains causing invasive disease, with domestic or household animals or with meat-production.…”
Section: Discussionmentioning
confidence: 99%
“…While NTS infection in HICs is generally associated with zoonotic transmission, the reservoirs and transmission route of the pathogens responsible for iNTS in SSA remains unknown. Seasonal patterns of iNTS, and the close domestic association of humans and animals in parts of SSA suggest that environmental factors could play a role [28,29]. Serotypes associated with iNTS have been isolated from animals in South Africa, although no genetic characterisation was carried out on these samples [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal patterns of iNTS, and the close domestic association of humans and animals in parts of SSA suggest a possible role for environmental factors [25,26]. Serotypes associated with iNTS have been isolated from animals in South Africa, although no genetic characterisation was carried out on these samples [27,28].…”
Section: Introductionmentioning
confidence: 99%